PARTICULAR FEATURES AND FUNCTIONS OF PEDAGOGICAL COMMUNICATION (Scientific journal of the Fergana State University, 2023)
The article is devoted to the peculiar features and functions of pedagogical communication. Communication is one of the most important factors in the psychological and social development of the student. The person-oriented technologies, influence and the structure of the pedagogical communication have been analyzed.